Potensi Jajanan Tradisional Dalam Mendukung Wisata Kuliner Di Kabupaten Bungo - Setiani, Rina Tri; wicaksono, nurzahra fathiyanabila; novalia, ratih juwita (Program Studi Pendidikan Vokasi Seni Kuliner, 2025)
This study aimed to describe the potential of traditional snacks in supporting culinary tourism in Bungo Regency, as well as to identify the challenges and preservation strategies. The research method used was descriptive qualitative, with data collection techniques through direct field observation, in-depth interviews with MSME actors, consumers, and the younger generation, as well as documentation related to the history and existence of traditional snacks. The data obtained were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study showed that traditional snacks such as kue muso, padamaran, takik beruk, kubang boyo and dodol tai minyak possess unique flavors, appearances, and cultural values that have the potential to become tourism attractions. These snacks are still used in traditional and official ceremonies, while also serving as the culinary identity of the region. The challenges faced include the influence of globalization, declining interest among the younger generation, limited innovation, and inadequate digital promotion. The suggested strategies include product and packaging innovation, digital-based promotion, culinary festivals, and the involvement of the younger generation.